451 Posterior Cingulate Theta Power as a Novel Biomarker of Mood. (April 2023) - Hacker, Carl; Brunner, Peter; Willie, Jon Timothy; Leuthardt, Eric C.
Abstract : INTRODUCTION: One third of patients with major depressive disorder (MDD) are refractory to standard therapies. Progress in therapeutic neuromodulation for depression has been challenging because of the widespread, network basis of mood and lack of neurophysiologic biomarkers. Neuroimaging studies of depression demonstrate increased connectivity within the default mode network (DMN), which subserves internal processes such as self-reflection, mind wandering, and memory. Invasive electrophysiology in the resting state has demonstrated that DMN connectivity corresponds to correlations in theta-band power. DMN activity is anti-correlated with the dorsal attention network (DAN) which, in contrast, subserves externally oriented cognition (i.e., top-down attention), and demonstrates alpha-specific resting-state correlations. METHODS: We used hourly, self-reported measures of mood and video facial affect recognition to estimate mood valence in six epilepsy patients undergoing invasive stereotactic electroencephalography monitoring. We analyzed power spectra and functional connectivity (band-limited power correlations) in epochs corresponding to mood estimates. Patients without substantial inpatient mood variability (n=3) were excluded. RESULTS: Depressed mood was correlated with increased theta power. This was most significant in electrodes within posterior cingulate cortex (DMN region; r = -0.58; p = 0.0007). Conversely, alpha power was increased during elevated mood, most significantly in the intraparietal sulcus (DAN region; r = 0.55, p = 0.0013). Theta connectivity was correlated with depressed mood (r = -0.53, p = 0.003) whereas alpha connectivity was correlated with elevated mood (r = 0.56, p = 0.002). CONCLUSIONS: Our results recapitulate the frequency specificity of resting-state physiology and encourage a network-based perspective of depression neurophysiology. Theta and alpha power within DMN and DAN networks, respectively, represent important biomarkers of mood and may guide neuromodulatory therapies. Posterior cingulate/precuneus cortex is a major DMN hub and should be sampled in future studies of neural correlates of mood.